Dapansutrile ameliorated chondrocyte inflammation and osteoarthritis through suppression of MAPK signaling pathway. (7th December 2022) - Tang, L; Sim, I; Moqbel, SAA; Wu, L
Introduction: Osteoarthritis (OA) is one of the most common joint diseases in the elderly population. Proinflammatory cytokines, such as Interleukin-1β (IL-1β), play an important role in the development and progression of OA. Dapansutrile is a specific inhibitor of the NOD-like receptor protein 3 (NLRP3) inflammasome and exhibits anti-inflammatory properties. Methods: In this study, we investigated the protective effect and the underlying mechanism of dapansutrile on cartilage degeneration in vitro and in vivo. In the present study, chondrocytes were isolated from rats and then were treated with dapansutrile. After that, the expression of ( Cox- 2, inducible nitric oxide synthase ( iNOS), Mmp -3, Mmp -9, Mmp -13 and IL -10) were evaluated at RNA level, then the expression of (COX-2, MMP-3, MMP-9, MMP-13, SOX-9 and COL2) were evaluated at protein level. Subsequently, the activation of the mitogen-activated protein kinase (MAPK) pathway was tested using western blotting (WB). Additionally, the rat OA model was developed to evaluate the protective effects of dapansutrile in vivo. Results: The results showed that dapansutrile had no obvious cytotoxicity on rat chondrocytes at 24 h (0, 1, 2, 5 and 10 μM). Dapansutrile significantly decreased IL-1β-induced upregulation of COX2, iNOS, matrix metalloproteinase 3 (MMP3), 9 (MMP9) and 13 (MMP13), and reversed IL-1β-induced the downregulation of IL-10, SOX9 and COL2. Dapansutrile also inhibited IL-1β-induced upregulation of the MAPK signaling pathway by downregulating the expression levels of phospho-ERK, and phospho-P38 in a concentration dependent manner. In addition, dapansutrile exhibited protective effects in rat OA model with lower Mankin's score and Osteoarthritis Research Society International (OARSI) score. Conclusion: Our study suggested that dapansutrile effectively inhibited chondrocyte inflammation by suppressing MAPK signaling pathway in vitro, and ameliorated cartilage degeneration in vivo, indicating an anti-inflammatory effect in OA treatment.